The Cellular and Molecular Effects of Fetoscopic Endoluminal Tracheal Occlusion in Congenital Diaphragmatic Hernia - Olutoye II, Oluyinka O.; Short, Walker D.; Gilley, Jamie; Hammond II, J. D.; Belfort, Michael A.; Lee, Timothy C.; King, Alice; Espinoza, Jimmy; Joyeux, Luc; Lingappan, Krithika; Gleghorn, Jason P.; Keswani, Sundeep G. (Frontiers in Pediatrics, 2022)
Congenital diaphragmatic hernia (CDH) is a complex disease associated with pulmonary hypoplasia and pulmonary hypertension. Great strides have been made in our ability to care for CDH patients, specifically in the prenatal improvement of lung volume and morphology with fetoscopic endoluminal tracheal occlusion (FETO). While the anatomic effects of FETO have been described in-depth, the changes it induces at the cellular and molecular level remain a budding area of CDH research. This review will delve into the cellular and molecular effects of FETO in the developing lung, emphasize areas in which further research may improve our understanding of CDH, and highlight opportunities to optimize the FETO procedure for improved postnatal outcomes.